GAYA HIDUP ANGGOTA AUTO CLUB DI PEKANBARU - Sicilia, Shandora; Yusuf, Yusmar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research will be done at the end of 2014 with the aim to know how life style members Auto Community, which is in Pekanbaru and to know what these factors that affect life style and how to spare time members use Auto Community, which is in Pekanbaru. Auto Club is a community social groups in the form that his members are not only to communicate but also interact. There is a process interaction in-depth in this group among the members that one and the other. Life style members Auto Club is generally well-known becomes hedonist. They were too materials to glorify the beauty, one of which is owned car.To find out the result, the authors use technical research data collection with observation, interviews and questionnaires. This research will be done in Pekanbaru Diponegoro Street condition will be taken as many as 1 club, namely TKCI Auto Club with the number of members as many as 40 people. I made 23 people from members TKCI as research respondents or samples.Results of these studies indicate that there had been on the member Auto Community Indonesia-Pekanbaru, Specific Toyota Kijang Club of Indonesia's influence ekstren Pekanbaru because of the influence of the environment and the media and added with a state financial The management that support them. spare time most of them using time to come together with their friends, but some of them there are some who spent time to spare to play games online and some of those seeking additional work as well as gardening or success and others.Result of this research is expected to be able to provide a clearer picture common to all parties that need information about life style members Auto Community Indonesia in Pekanbaru.Key words : Life style, Auto Community, the consumption, spare time